High Responsivity and Photovoltaic Effect Based on Vertical Transport in Multilayer α‐In2Se3. Issue 5 (14th January 2020) - Mech, Roop K.; Mohta, Neha; Chatterjee, Avijit; Selvaraja, Shankar Kumar; Muralidharan, Rangarajan; Nath, Digbijoy N.
Abstract : Herein, device demonstration based on vertical transport in multilayer α‐In2 Se3 is reported. Photodetectors realized using a metal/α‐In2 Se3 /indium tin oxide (ITO) vertical junction exhibit clear signature of the band edge in spectral responsivity. The wavelength at 680 nm corresponding to an ultrahigh responsivity of 1000 A W −1 and a detectivity of >10 13  cm Hz 0.5  W −1 at a bias of 0.5 V. The variation of responsivity and detectivity with optical power density is studied, and a transient response of 20 ms is obtained for the devices (instrument limitation). In addition, an asymmetric barrier height arising out of ITO and Au contacts to a vertical α‐In2 Se3 junction resulted in a photovoltaic effect with V OC ≈0.1 V and I SC ≈0.4 μA under an illumination of 520 nm. Abstract : A vertical metal–semiconductor–metal photodetector implemented using α‐In2 Se3 flake is studied. The proposed photodetector attains a very high spectral responsivity and detectivity at a visible wavelength of 680 nm. An asymmetric barrier arising out of ITO and Au contacts results in photovoltaic effect. The results reveal the photodetector as a suitable candidate for ultrasensitive detection.